Growth mechanism of titanium monoxide TiOx on a reduced calcium titanate CaTi2O4 surface. (3rd December 2015) - Guo, Cong; Sheng, Huaping; Ma, Yurong; Jin, Lei; Jia, Shuangfeng; Zheng, He; Liu, Yong; Shi, Jing; Wang, Jianbo
Abstract : This paper presents an electron microscopy study of reduced calcium titanate crystals (CaTi2 O4 ) and the growth mechanism of titanium monoxide TiO x on a CaTi2 O4 surface. Large high‐quality CaTi2 O4 crystals were prepared using the molten salt flux method. The crystallographic directions and the growth direction of the CaTi2 O4 crystalline needles were confirmed by electron backscatter diffraction and Kikuchi pattern analysis. The low‐angle grain boundaries in CaTi2 O4 and the crystallographic orientation relationship between CaTi2 O4 and TiO x were investigated using high‐resolution transmission electron microscopy. It is found that both the low‐angle boundaries and the amorphous area may play a key role during the growth process of titanium monoxide TiO x . The results presented here contribute to a better understanding of the detailed growth mechanism of TiO x on a CaTi2 O4 surface.